2014
DOI: 10.1002/mrc.4121
|View full text |Cite
|
Sign up to set email alerts
|

Examination of amber and related materials by NMR spectroscopy

Abstract: Examination of the solid-state (13)C and solution (1)H NMR spectra of fossilized resins (ambers) has generated five groupings of materials based on spectral characteristics. The worldwide Group A is associated with the botanical family of the Araucariaceae. The worldwide Group B is associated with the Dipterocarpaceae. Baltic amber or succinite (Group C) is related to Group A but with a disputed conifer source. Amber from Latin America, the Caribbean, and Africa is associated with the Fabaceae, the genus Hymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Specifically, these resins correspond to the Class Ib resins first classified with Py-GC-MS by Anderson et al (1992). 13 C solid-state NMR has revealed a consistent spectral signature from numerous modern and fossil Class Ib resins the world over; these correspond to Group A (see Lambert et al, 2008Lambert et al, , 2015. This is indicated by comparable aliphatic, olefinic and carbonyl regions and the absence of any significant succinic acid resonances at 170 ppm (which are characteristic of Class Ia resins).…”
Section: Chatham Amber Classification: 13 C Solid-state Nmrmentioning
confidence: 76%
See 1 more Smart Citation
“…Specifically, these resins correspond to the Class Ib resins first classified with Py-GC-MS by Anderson et al (1992). 13 C solid-state NMR has revealed a consistent spectral signature from numerous modern and fossil Class Ib resins the world over; these correspond to Group A (see Lambert et al, 2008Lambert et al, , 2015. This is indicated by comparable aliphatic, olefinic and carbonyl regions and the absence of any significant succinic acid resonances at 170 ppm (which are characteristic of Class Ia resins).…”
Section: Chatham Amber Classification: 13 C Solid-state Nmrmentioning
confidence: 76%
“…This is indicated by comparable aliphatic, olefinic and carbonyl regions and the absence of any significant succinic acid resonances at 170 ppm (which are characteristic of Class Ia resins). Class Ib (or Group A) fossil resins are consistently associated with conifers, particularly Araucariaceae (Anderson et al, 1992;Lambert et al, 1993Lambert et al, , 2008Lambert et al, , 2015, but a broader range of botanical sources have been proposed, most notably: Cupressaceae (Anderson et al, 1992;Anderson and Lepage, 1995;Anderson, 2006). To date, Group A amber has been associated only with resins of Araucariaceae (e.g., the copious resin-producer Agathis australis, New Zealand; Lambert et al, 1993).…”
Section: Chatham Amber Classification: 13 C Solid-state Nmrmentioning
confidence: 99%
“…Schub., which together with oak in the Eocene, dominated the humid mixed forest cover of Northern and Central Europe. More recent work on the chemical composition of Baltic amber has also suggested that trees within the family Araucariaceae or Sciadopityaceae might be candidates for the production of this amber deposit (Langenheim, 2003;Wolfe et al, 2009;Lambert et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Schub., which together with oak in the Eocene dominated the humid mixed forest cover of Northern and Central Europe. More recent work on the chemical composition of Baltic amber has also suggested that trees within the family Araucariacea or Sciadopityaceae might be candidates for the production of this amber deposit (Langenheim 2003;Wolfe et al 2009;Lambert et al 2014).…”
Section: Methodsmentioning
confidence: 99%